Sifting through the weeds: Relationships between cannabis use frequency measures and delay discounting. (January 2021) - Sofis, Michael J.; Borodovsky, Jacob T.; Pike, Chelsea K.; Liu, Lili; Jacobson, Nicholas C.; Budney, Alan J.
Highlights: The relationships among DD and four frequency of cannabis use indices were compared. DD showed a significant positive relationship with three of the four use indices. A latent class analysis was designed to find more meaningful patterns of use. Measures with narrower timeframes, and not latent classes, related best to DD. Use measures with narrow time frames may illuminate how DD relates to cannabis use. Abstract: Background: Delay Discounting (DD) relates to more frequent cannabis use, but results are variable, potentially because of variations in whether integrated or single-item measures are used, and whether the timeframe of measures is narrow or broad. Explicating the relationship between DD and cannabis use may result from comparing use indices that vary on these characteristics. Methods: This online study of current cannabis users ( n  = 1, 800) assessed DD and three cannabis use frequency items: number of days of use in the past month, times used per day, and weekly-monthly use. A fourth index derived with Latent Class Analysis (LCA) integrated days per month and times per day to try to better characterize frequency patterns. Effect sizes reflecting relations between cannabis use frequency indices and DD were compared. Results: Three frequency classes emerged from the LCA (Low-Moderate-High). DD was significantly associated with times per day ( r  = 0.11, d  = 0.21), days of use ( r  = 0.09, d  = 0.18), and the LCA index ( r  = 0.06, d  = 0.13), but not weekly-monthly use ( r  = 0.04, d  = 0.09). Times per day was more strongly related to DD than LCA classes ( p  < 0.01) and weekly-monthly use ( p  < 0.05), but not days of use ( p  = 0.66). Days of use exhibited a stronger relationship with DD than weekly-monthly use (p < 0.001), but not LCA classes ( p  = 0.06). Conclusions: Cannabis use frequency measures with narrower timeframes may demonstrate stronger positive relationships to DD. The LCA index did not improve the relationship between frequency and DD, potentially because of shared variance between use days and times per day. Specific characteristics of cannabis use frequency may be particularly indicative of excessive DD.